Study of the interaction of the GSB-106 BDNF neurotrophin dipeptide mimetic with the TrkB tyrosine kinase receptor using surface plasmon resonance technology - A. V. Tarasiuk; Y. V. Mezentsev; O. V. Gnedenko; P. Yu. Povarnina; A. S. Ivanov (LLC "Publisher OKI", 2023)
The interaction of the neurotrophin BDNF dipeptide mimetic, compound GSB-106, with the tyrosine kinase TrkB receptor specific for the fullsized neurotrophin was studied using surface plasmon resonance. The significant decrease in the binding of BDNF to TrkB, which was preincubated with GSB-106, was shown. The obtained data indicate the interaction of GSB-106 with the TrkB receptor.